2019
DOI: 10.1021/acs.est.9b04604
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl Substances in Drinking Water, Indoor Air and Dust from Ireland: Implications for Human Exposure

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 37 publications
5
32
1
Order By: Relevance
“…PFOA was detected at higher concentrations in this study than in the UK (Goosey and Harrad, 2012), at both landfill and reference locations in Germany (Weinberg et al, 2011), and in Canada (Shoeib et al, 2011). This is consistent with our recent report that concentrations of PFOA in Irish indoor air exceed those reported elsewhere (Harrad et al, 2019b) and combined, these observations suggest extensive use of PFOA in Ireland. In contrast, concentrations of PFOS and PFHxS in this study are lower than those reported in outdoor air at a number of UK locations (Goosey and Harrad, 2012).…”
Section: Samplessupporting
confidence: 92%
See 2 more Smart Citations
“…PFOA was detected at higher concentrations in this study than in the UK (Goosey and Harrad, 2012), at both landfill and reference locations in Germany (Weinberg et al, 2011), and in Canada (Shoeib et al, 2011). This is consistent with our recent report that concentrations of PFOA in Irish indoor air exceed those reported elsewhere (Harrad et al, 2019b) and combined, these observations suggest extensive use of PFOA in Ireland. In contrast, concentrations of PFOS and PFHxS in this study are lower than those reported in outdoor air at a number of UK locations (Goosey and Harrad, 2012).…”
Section: Samplessupporting
confidence: 92%
“…Turning to PFASs, our concentrations in groundwater are well below those reported in Irish landfill leachate (Harrad et al, 2019a), but fall within a similar range to those reported for Irish tapwater (Harrad et al, 2019b). Consistent with the predominance of PFOA in air and soil observed in this study, PFOA is the dominant PFAS of those targeted here, being the only PFAS detected in all samples and at concentrations exceeding those of other PFASs.…”
Section: Samplessupporting
confidence: 88%
See 1 more Smart Citation
“…Extraction of breast milk samples was performed based on methods previously published by Kärrman et al (2006). For consistency with our measurements of PFASs in Irish drinking water, indoor air and dust (Harrad et al, 2019b); in addition to PFOS, PFOA, PFNA, and PFHxS, we measured the following other PFASs: perfluorobutane sulfonate (PFBS), perfluorooctane sulfonamide (FOSA), its methyl and ethyl derivatives (MeFOSA and EtFOSA), as well as methyl and ethyl perfluorooctane sulfonamido ethanols (MeFOSE and EtFOSE). Five mL of breast milk were added to a centrifuge tube and spiked with 20 µL of an internal standard solution (containing 1 ng/µL of M8PFOS, M8PFOA, M8FOSA, MPFHxS, MPFNA, d-N-MeFOSA, d-N-EtFOSA in methanol).…”
Section: Sample Preparation and Analysis Extraction And Clean-upmentioning
confidence: 88%
“…Current understanding of the pathways of human exposure to PFASs is that whilst diet constitutes the principal pathway for most individuals, indoor air and dust play minor but potentially significant roles (Harrad et al, 2010), with drinking water representing a potentially important additional source of exposure to PFASs (Jian et al, 2017). As part of the ELEVATE project funded by the Environmental Protection Agency of Ireland, we recently reported concentrations of brominated flame retardants (BFRs), PFOS, PFOA, PFHxS, PFNA, and other PFASs in drinking water, and in indoor air and dust from cars, homes, offices and school classrooms in the Republic of Ireland (Harrad et al, 2019b;Wemken et al, 2019). Inter alia, by multiplying our data on concentrations of PFASs by exposure factors (e.g.…”
Section: Introductionmentioning
confidence: 99%